β‐Catenin activity induces an RNA biosynthesis program promoting therapy resistance in T‐cell acute lymphoblastic leukemia - Violeta García‐Hernández; David Arambilet; Yolanda Guillén; Teresa Lobo‐Jarne; María Maqueda; Christos Gekas; Jessica González; Arnau Iglesias; Nerea Vega‐García; Inés Sentís; Juan L Trincado; Ian Márquez‐López; et al. (EMBO Molecular Medicine)
Abstract Understanding the molecular mechanisms that contribute to the appearance of chemotherapy resistant cell populations is necessary to improve cancer treatment. We have now investigated the role of β‐catenin/CTNNB1 in the evolution of T‐cell Acute Lymphoblastic Leukemia (T‐ALL) patients and its involvement in therapy resistance. We have identified a specific gene signature that is directly regulated by β‐catenin, TCF/LEF factors and ZBTB33/Kaiso in T‐ALL cell lines, which is highly and significantly represented in five out of six refractory patients from a cohort of 40 children with T‐ALL. By subsequent refinement of this gene signature, we found that a subset of β‐catenin target genes involved with RNA‐processing function are sufficient to segregate T‐ALL refractory patients in three independent cohorts. We demonstrate the implication of β‐catenin in RNA and protein synthesis in T‐ALL and provide in vitro and in vivo experimental evidence that β‐catenin is crucial for the cellular response to chemotherapy, mainly in the cellular recovery phase after treatment. We propose that combination treatments involving chemotherapy plus β‐catenin inhibitors will enhance chemotherapy response and prevent disease relapse in T‐ALL patients.